Endothelial function and arterial stiffness indexes in subjects with acute ischemic stroke: Relationship with TOAST subtype - Tuttolomondo, Antonino; Casuccio, Alessandra; Della Corte, Vittoriano; Maida, Carlo; Pecoraro, Rosaria; Di Raimondo, Domenico; Vassallo, Valerio; Simonetta, Irene; Arnao, Valentina; Pinto, Antonio (Atherosclerosis, 2017)
Only one study has examined endothelial function in subjects with acute ischemic stroke and no study has yet assessed arterial stiffness and reactive hyperemia peripheral arterial tonometry (RH-PAT) in ischemic stroke and its clinical subtypes. Our study aimed to evaluate arterial stiffness and endothelial dysfunction indexes in patients with acute ischemic stroke and the relationship between endothelial dysfunction indexes and arterial stiffness markers and stroke subtypes according to Trial of Org 10172 in Acute Stroke Treatment (TOAST) Classification. We enrolled 98 patients with a diagnosis of acute ischemic stroke and 105 hospitalized patients without a diagnosis of acute ischemic stroke. Arterial stiffness analysis was conducted by applanation tonometry to record radial artery pressure waveform continuously; augmentation index (Aix) and pulse wave velocity (PWV) were calculated. The reactive hyperemia index (RHI) was assessed by peripheral arterial tonometry. In comparison to controls, ischemic stroke subjects had higher mean levels of PWV, Aix, and significantly lower mean RHI values. Compared to subjects with lacunar and cardioembolic stroke, those with Large Artery AtheroSclerosis (LAAS) subtype of stroke had higher median levels of PWV and significantly lower median levels of RHI. On multinomial logistic regression analysis of predictive variables of stroke subtype (lacunar vs. LAAS and lacunar vs. cardioembolic), we observed a negative association between RHI value and LAAS subtype and a negative association of PWV with cardioembolic subtype. Our findings underline the relationship between endothelial and arterial stiffness index correlations in patients with acute ischemic stroke, also suggesting the use of a combination of PAT and arterial stiffness indexes to better categorize patients with ischemic stroke. •No study has analyzed endothelial function indexes in ischemic stroke using RH-PAT.•Subjects with acute ischemic stroke showed higher mean levels of PWV and Aix.•Subjects with acute ischemic stroke showed significantly lower mean RHI values.•Patients with LAAS subtype of ischemic stroke had higher mean levels of PWV values.•Patients with LAAS subtype of ischemic stroke lower mean levels of RHI value.